Education and the Risk Society
XVI, 292 p.
Keywords: Sociological and anthropological literature has examined how contemporary western society has become a “risk society.” Education and the Risk Society is the first volume to explore this seminal concept through the lens of education. Drawing on a theoretical literature that has great potential as a lens to view changes in neoliberal discourses of global capitalism from both critical and generative perspectives, Education and the Risk Society presents situated, empirical studies investigating an uncertain world as people practice it on the ground, through language and activity, within educational settings.